Local administration of Mitomycin-C-Treated peripheral blood mononuclear cells (PBMCs) prolongs allograft survival in vascularized composite allotransplantation - Radu, Christian Andreas; Gebhard, Martha-Maria; Germann, Günter; Terness, Peter (Microsurgery, 2016)
Background: VCA offers a potential treatment for extensive tissue defects. First results of systemic administration of Mitomycin C-treated PBMCs in VCA demonstrated a significant prolongation of allograft survival. The aim of this study is to evaluate if local administration of MMC-PBMCs prolongs allograft survival in allogeneic hind limb transplantations of the rat. Methods: Sixty allogeneic hind limb transplantations in the rat were performed in six groups. Lewis rats (LEW) were used as hind limb donors and Brown-Norway rats (BN) as recipients. Animals in group A received donor-derived MMC-treated PBMCs locally (i.m.). Group B received no immunosuppressive therapy, group C received a standard immunosuppressive regime consisting of FK506 and Prednisolon, group D (BN to BN) comprised isograft transplantations without immunosuppressive treatment, group E received non-treated PBMCs (i.m.) and group F received phosphate buffered saline (PBS) without cells. The transplanted hind limbs were assessed for color, edema, skin, hair condition, and consistency of the thigh every 8 hours. Results: Rejection in group A was delayed to an average of 7.2 ± 0.6 days. Survival times were significantly prolonged (P < 0.01) compared to control groups B, E, and F (5.5 ± 0.7, 5.8 ± 0.7, and 5.7 ± 0.5 days). Control groups C and D showed no signs of rejection. Conclusion: The findings of this study show that local administration of MMC-PBMCs has no side effects and significantly extends allograft survival. Further experiments with MMC-PBMCs treatments repeated at different time-points and being added to low dose immunosuppressive protocols need to be performed to improve experimental and eventually clinical outcome after VCA. © 2015 Wiley Periodicals, Inc. Microsurgery 36:417-425, 2016.
Published online: 17 November 2015
Gesehen am 02.02.2018